Friction and Wear Properties of CrAl-Based Coatings for Nuclear Fuel Cladding - Ma, Biao; Luo, Bin; Wang, Zhuozheng; Meng, Chuiyi; He, Xiujie (Frontiers in Energy Research, 2021)
Friction and wear performance is one of the key mechanical properties of accident tolerant fuel cladding coatings. In this study, reciprocating sliding wear tests had performed on two types of CrAl and CrAlN coatings with two different Al content ratios and Zircaloy-4. The coefficient of friction, wear depth, and abrasion loss were measured and compared. The results indicated that the CrAl-based coatings improve the wear behavior significantly and nitrogen has an obvious improvement on the wear resistance of the coating. The friction and wear performance was also studied in a water environment. The results show that the presence of water degrade the wear performance of Zircaloy-4 and CrAl coatings but ameliorates the friction and wear performance of CrAlN coatings. The feasibility of depositing ATF coating on conventional Zr substrates to mitigate the influence of grid-to-rod fretting was demonstrated.